COVID-19 vaccination influences subtypes of γδ-T cells during pregnancy - Wang, Li; Li, Jiawei; Jiang, Silin; Li, Yan; Guo, Rong; Chen, Yuyuan; Chen, Yan; Yu, Hang; Qiao, Qingqing; Zhan, Mingjie; Yin, Zhinan; Xiang, Zheng; et al. (Frontiers in Immunology, 2022)
Up to now, there is insufficient clinical data to support the safety and effects of vaccination on pregnancy post COVID-19 vaccination. The γδ-T cells are considered as important component in immune system to against viral infection and exhibit critical roles through pregnancy period. However, the immunological roles of γδ-T cells in the pregnant women with COVID-19 vaccination remain unclear. Therefore, the objective of this study is to investigate the alteration of frequency and expression pattern of activation receptors and inhibitory receptors in γδ-T cell and its subsets in peripheral blood samples collected from non-pregnancy vaccinated women, vaccinated pregnant women and unvaccinated pregnant women. Our findings indicated that the frequency of CD3+γδ-T+ cells is lower in vaccinated pregnant women than that in unvaccinated pregnant women. But, no significant difference was found in the frequency of CD3+γδ-T+ cells between non-pregnancy vaccinated women and vaccinated pregnant women. In addition, there were not significant differences in the frequencies of CD3+γδ-T+Vδ1+T cells, CD3+γδ-T+Vδ2+T cells, CD3+γδ-T+Vδ1-Vδ2-T cells and Vδ1+T cell/Vδ2+T cell ratio between the pregnant women with or without COVID-19 vaccination. Similar results were found after comparing non-pregnant and pregnant women who received the COVID-19 vaccine. However, there was a significant difference in the fraction of Vδ1-Vδ2-T cells in CD3+γδ-T+ cells between non-pregnancy vaccinated women and vaccinated pregnant women. The frequency of NKG2D+ cells in Vδ2+T cells was not significant differences in the vaccinated pregnant women when compared to that in unvaccinated pregnant women or non-pregnancy vaccinated women. But, the percentage of NKG2D+ cells in Vδ1+T cells was the lowest in the pregnant women after COVID-19 vaccination. Furthermore, down-regulation of NKP46 and NKP30 were found in Vδ2+T and Vδ1+T cells in the vaccinated pregnant women, respectively. After the vaccination, up-regulation of PD-1 expression in Vδ1+T cells and Vδ2+T cells indicated γδ-T cells could respond to COVID-19 vaccination and display an exhausted phenotype following activation. In conclusion, COVID-19 vaccination influences subtypes of γδ-T cells during pregnancy, but the side effects might be limited. The phenotypical changes of Vδ1+T cells and Vδ2+T cells will be a promising predictor for evaluating clinical outcome of COVID-19 vaccine.